Impact of the COVID-19 Pandemic on The Development of Digital Services in The Activities of The Museums - Anna KOLASINSKA; Matylda SIWEK (Communications of International Proceedings, 2021)
The COVID-19 pandemic influenced almost all industries and fields, including tourism and culture. Digital technology has more than ever increased the potential value of cultural heritage and offered new possibilities both for the institutions and visitors. The purpose of this article was to compare the use of digital services by museums and art galleries located in the historical city of Krakow before and during COVID-19 pandemic (in between the third and fourth wave). The research included an in-depth analysis of the websites of all museums in Krakow (n=64) and Google Play was used to verify if they are up to date. The research showed that some e-services were found to be more accessible compared to the pre-pandemic period, however, the number of museums that allow for booking a visit online (exact hour) has decreased. There is no difference in the number of museums offering mobile applications.
Keywords: museums; Krakow; digital services; COVID-19; online